Dopamine genetic risk score predicts impulse control behaviors in Parkinson’s disease - Alison Hall; Samuel R. Weaver; Lindsey J. Compton; Winston D. Byblow; Ned Jenkinson; Hayley J. MacDonald (Clinical Parkinsonism & Related Disorders, 2021)
Introduction: Up to 40% of Parkinson’s disease patients taking dopamine agonist medication develop impulse control behaviors which can have severe negative consequences. The current study aimed to utilize dopamine genetics to identify patients most at risk of developing these behaviors. Methods: Demographic, clinical, and genetic data were obtained from the Parkinson’s Progression Markers Initiative for de novo patients (n = 327), patients taking dopamine agonists (n = 146), and healthy controls (n = 160). Impulsive behaviors were identified using the Questionnaire for Impulsive-Compulsive Disorders in Parkinson’s Disease. A dopamine genetic risk score was calculated for each patient according to polymorphisms in genes coding for dopamine D1, D2 and D3 receptors, and catechol-O-methyltransferase. A higher score reflected higher central dopamine neurotransmission. Results: Patients on agonists with a low dopamine genetic risk score were over 18 times more likely to have an impulsive behavior compared to higher scores (p = 0.04). The 38% of patients taking agonists who had at least one impulsive behavior were more likely to be male and report higher Unified Parkinson’s Disease Rating Scale I&II scores. With increasing time on dopamine agonists (range 92–2283 days, mean 798 ± 565 standard deviation), only patients with a high dopamine genetic risk score showed an increase in number of impulsive behaviors (p = 0.033). Predictive effects of the gene score were not present in de novo or healthy control. Conclusions: A dopamine genetic risk score can identify patients most at risk of developing impulsive behaviors on dopamine agonist medication and predict how these behaviors may worsen over time.